Actantial And Functional Model In Perempuan Yang Menangis Kepada Bulan Hitam : Greimas’ Naratology - Dewi, Maharani; Yasin, Mohammad Ilham; Fikri, Moh. Hilman (International Journal of Sustainable English Language, Education, and Science, 2025)
This study applies qualitative methods in the process of data collection and analysis. This study aims to analyze the story's structure in Dian Purnomo's novel, Perempuan Yang Menangis Kepada Bulan Hitam, using Greimas' narratological perspective. Greimas divides two structural models of narratology in his theory. The two models are the actantial model and the functional model. Two narratological models from Greimas aim to reveal the story's structure, showing the connection between women who are subject actants to get objects, so that the actors who become objects can show their strength as women. The study results show Magi Diela as an actant who becomes the Subject to fight for her freedom as a woman who becomes the Object. Magi Diela, as an actant charged with the task of being a subject, can show her power over her mind and body as a woman and leave the cultural discrimination she has received through Kawin Tangkap Culture. Although this is not an easy process, Magi Diela, as a subject, has to go through various situations that are exhausting both physically and psychologically. The results of the second model, namely the functional model, show three stages in which Magi must struggle as an actant burdened as a subject in the actantial model to get an object. The three stages of the functional structure model that Magie went through proved that she had managed to overcome her difficulties and misfortunes as a woman who lived in restraint and demonstrated the freedom she strived for.